2013
DOI: 10.1038/srep01819
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Characteristics of Copper Ion-Modified DNA Thin Films

Abstract: We developed a new method of fabricating a divalent copper ion (Cu2+) modified DNA thin film on a glass substrate and studied its magnetic properties. We evaluated the coercive field (Hc), remanent magnetization (Mr), susceptibility (χ), and thermal variation of magnetization with varying Cu2+ concentrations [Cu2+] resulting in DNA thin films. Although thickness of the two dimensional DNA thin film with Cu2+ in dry state was extremely thin (0.6 nm), significant ferromagnetic signals were observed at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The ions were added to the DNA sample solution after completing the DNA hybridization in order to avoid the structural deformation of the DNA nanolattices due to the presence of ions at a relatively higher concentration than the optimum ion-doping concentration due to the presence of excess ions (up to an optimum ion-doping concentration, DNA lattice periodicities were observable and above, DNA lattice were not formed properly so that lattice periodicities were hardly observable). A stepwise addition of the ions into the DNA samples revealed that the optimum ion doping concentrations for the DNA nanolattices were of 2 mM for Ni 2+ and 1 mM for Dy 3+ [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…The ions were added to the DNA sample solution after completing the DNA hybridization in order to avoid the structural deformation of the DNA nanolattices due to the presence of ions at a relatively higher concentration than the optimum ion-doping concentration due to the presence of excess ions (up to an optimum ion-doping concentration, DNA lattice periodicities were observable and above, DNA lattice were not formed properly so that lattice periodicities were hardly observable). A stepwise addition of the ions into the DNA samples revealed that the optimum ion doping concentrations for the DNA nanolattices were of 2 mM for Ni 2+ and 1 mM for Dy 3+ [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…The dopant ions are distributed to DNA almost randomly assuming that the binding probabilities of the dopant to G-C, A-T and (PO 4 ) − are similar (33%) in contrast to Dugasani et al [19].…”
Section: Doping Processmentioning
confidence: 93%
“…Doping process is required to start after the successful finish of former work. Dugasani et al [19] suggested the most probable locations of subsequent dopant ions between base pairs and PO4, and at last, the random displacement of dopants instead of hydrogen atoms of N-H-N and N-H-O.…”
Section: Constructing Modified Dna Nanowiresmentioning
confidence: 99%
See 2 more Smart Citations